Cultivating gentlemen : the meaning of country life among the Boston elite, 1785-1860 - Thornton, Tamara Plakins, 1957- (Yale University Press, 1989)
Between the Revolution and the Civil War, many merchants, financiers, manufacturers, lawyers, and politicians of Boston's elite settles on country estates, took up gentleman farming, and founded agricultural and horticultural societies. It is a curious fact of history that these men, who were directly responsible for changing the Massachusetts economy from a farming to a commercial and industrial one, spent so much time identifying themselves with things rural and agrarian. In this lively and well-illustrated book, Tamara Plakins Thornton documents the rural pursuits and argues that elite Bostonians drew on their rich reservoir of associations to characterize themselves as virtuous members of a legitimate American elite.Thornton traces this history in the papers of elite Bostonians and their agricultural and horticultural institutions and by looking at the contemporary literature on agricultural reform, stockbreeding, and horticulture. Her investigations provide new and unexpected pictures: George Cabot, the quintessential Federalist merchant and statesman, attending to potatoes on his secluded Brookline farm; Josiah Quincy, a congressman, mayor of Boston, and Harvard president, calculating the yields of carrots on his estate; Nathaniel Ingersoll, an East India merchant, enthusiastically reporting the design of his model piggery to a Boston agricultural periodical. By participating in such activities, these men and others like them sought to justify their privileged status in "egalitarian" America, counter charges of boorishness and materialism, and adjust to the disturbing economic and social changes they themselves had set in motion.Tamara Plakins Thornton is assistant professor of history at State University of New York at Fredonia.